Crowdsourcing your brand how to tap customer desire - Libert, Barry (FTPress Delivers elements, 2010)
This Element is an excerpt from We Are Smarter Than Me: How to Unleash the Power of Crowds in Your Business (9780132244794) by Barry Libert and Jon Spector. Available in print and digital formats. Get your customers to help you build your brand, enhance your offerings, and broaden your base of buyers! There are several ways your company can tap the priceless desire of customers to expand your product or service base. Starting with MasterCard, a pioneer in tapping the online community for help in selling services and products, a few examples are included ...